Investigation on the feasibility and performance of ground source heat pump (GSHP) in three cities in cold climate zone, China. (December 2015) - Liu, Zhijian; Xu, Wei; Qian, Cheng; Chen, Xi; Jin, Guangya
Abstract: As a renewable energy technology, ground source heat pump (GSHP) system is high efficient for heating and cooling in office buildings. However, this technology has strong dependence on the meteorological and building envelope thermal characteristic parameters. For the purpose of quantitative investigation on the feasibility and performance GSHP, three cities located in cold climate zone, Qiqihaer, Shenyang and Beijing, were sampled. Firstly, the office building dynamic loadings in these cities were calculated on basis of the different meteorological and envelope thermal characteristic parameters. The TRNSYS, one kind of energy simulation software, were employed to simulate the operation performances of GSHP on basis of these parameters. The simulation revealed the data on the outlet/inlet temperature of buried pipes, soil temperature, energy consumption distribution and the coefficient of performance (COP) for one year operation. Furthermore, ten years operation was also simulated to show the stability of the performance based on the outlet/inlet temperature of buried pipes and soil temperature. From these results, the GSHP had shown its most suitable performance in Beijing, second in Shenyang and worst in Qiqihaer. These results could be used as a reference on suitable utilization of GSHP systems in office buildings located in cold climate zone, China. Highlights: GSHP should be carefully evaluated before using in Chinese cold climate zone. The meteorological parameters had great impact on GSHP performance and feasibility. The building envelope characteristic also affected GSHP performance and feasibility. Soil temperature for ten years simulation was vital to evaluated GSHP performance. Temperature of inlet/outlet of buried pipes for ten years was also vital for this.